Adolescent Idiopathic Scoliosis and Mental Health Disorders: A Narrative Review of the Literature - Ioanna Mitsiaki; Athanasios Thirios; Eleni Panagouli; Flora Bacopoulou; Dimitris Pasparakis; Theodora Psaltopoulou; Theodoros N. Sergentanis; Artemis Tsitsika (MDPI AG, 2022)
Adolescent idiopathic scoliosis (AIS) is the most common type of scoliosis. The condition begins in puberty, affects 1-4% of adolescents, and disproportionately affects young women. Our aim was to comprehensively examine the association between AIS and risk for depression, anxiety, eating disorders, psychotic disorders, and personality dysfunctional mechanisms. Methods: Literature review of related articles published in PubMed, Google Scholar, and Scopus up to 15 July 2021. Results: A total of 30 studies were deemed eligible, examining the effects of AIS upon mental health, and using appropriate psychometric inventories. Studies highlighted the association of brace treatment with elevated anxiety. In addition, mental health conditions and traits (e.g., anxiety and depressive symptoms, neuroticism) were detected more frequently amongst AIS patients compared to healthy controls. Conclusions: AIS represents a risk factor for mental health disorders. More longitudinal studies, utilizing accurate psychometric instruments, are warranted, to reveal the current impact of AIS on the mental health of youngsters, along with the tailoring of well-targeted interventions to reduce the burden of mental health issues in adulthood.